Linhas de fuga do Antropoceno: ontologias não-modernas e os antípodas da Razão - António Carvalho; Mariana Riquito (e-cadernos ces)
This experimental article departs from the current controversy of the Anthropocene to reflect on alternatives to modern Western rationality, highlighting the need to develop non-modern ontologies to face the current climate and environmental crisis. A series of heterogeneous examples are used – from contemplative practices, altered states of consciousness to planetary models – to reflect on the connection between humans, terrestrial systems and their bodies. These examples are seen as allegories that put us face to face with the disruptive character of the Anthropocene, contrasting with the dominant ontologies of Western modernity. The article aims to carry out a performative and provocative exercise to produce alternative ways of “reacting” to the Anthropocene beyond cognition and representation, combining different epistemological and disciplinary registers – sometimes within the limits of conventional academic language – that are understood as lines of escape, thus launching the motto for this issue of e-cadernos CES.